An Empirical Investigation of Leader Motivating Language and Voluntary Work Behaviors in the Healthcare Sector of Pakistan - Sara Sabir (Journal of Management Practices, Humanities and Social Sciences, 2024)
The performance of nurses and doctors is vital for the proper functioning of the healthcare system of any country and for providing quality care to patients. However, the working of the healthcare personnel in Pakistan has deteriorated over previous years, and they are engaged in more negative workplace behaviors. The current study examines the direct effect of leader-motivating language on counterproductive work behavior. The indirect mediating effect of perceived interactional justice is also examined in this relationship. Purposive sampling was used to collect the data from 440 healthcare staff working in hospitals operating in the Multan region, Pakistan. The analysis was done using SPSS and the hypotheses were tested with PROCESS macro technique. The results supported the four hypotheses developed for the study and it was proved that leader motivating language has significant impact on both counterproductive work behavior and perceived interactional justice. Moreover, interactional justice was also significantly related to counterproductive work behavior. The mediating effect of perceived interactional justice was also confirmed. The study contributes to Motivating language theory by investigating the proposed new integration of variables and establishing the underlying mechanism of interactional justice. The findings of the study are practically useful for the hospitals so that negative behaviors among staff can be reduced and overall effectiveness can be improved.